Fabrication of Coaxial Wet‐Spun Graphene–Chitosan Biofibers1. Issue 2 (22nd July 2015) - Mirabedini, Azadeh; Foroughi, Javad; Thompson, Brianna; Wallace, Gordon G.
Abstract : One‐step continuous wet‐spinning of coaxial electroactive fibres of chitosan/graphene oxide (Chit/GO) via a facile method is introduced for the first time, eliminating the need for post‐treatment processes. Spinnability of coaxial fibres as well as their characterization for several properties is investigated. L‐ascorbic acid was found to reduce graphene oxide under mild conditions to create conductivity in the final fibre. As‐prepared fibres were found to be cytocompatible with good electrical conductivity and mechanical properties. SEM images from the cross‐section of Chit/GO fibres showed an irregular shaped multifilament GO fibre covered with a cylinder‐shaped sheath of chitosan. Coaxial fibres had an ultimate tensile stress and elastic modulus that increased 8 500% and 3 350%, respectively compared to the graphene oxide fibres alone. Abstract : The novel technique of coaxial wet‐spinning is employed for the fabrication of electroactive biofibres of chitosan/graphene oxide in a basic coagulation bath. As‐prepared fibres were found to be cytocompatible with good electrical conductivity and mechanical properties. The results imply that the developed fibres hold a great promise in applications such as drug delivery, batteries and tissue scaffolds in nearby future.